Reduction of inflammation and mitochondrial degeneration in mutant SOD1 mice through inhibition of voltage-gated potassium channel Kv1.3 - Ratano, Patrizia; Cocozza, Germana; Pinchera, Cecilia; Busdraghi, Ludovica Maria; Cantando, Iva; Martinello, Katiuscia; Scioli, Mariarosaria; Rosito, Maria; Bezzi, Paola; Fucile, Sergio; Wulff, Heike; Limatola, Cristina; et al. (Frontiers in Molecular Neuroscience, 2024)
Amyotrophic lateral sclerosis (ALS) is a fatal neurodegenerative disease with no effective therapy, causing progressive loss of motor neurons in the spinal cord, brainstem, and motor cortex. Regardless of its genetic or sporadic origin, there is currently no cure for ALS or therapy that can reverse or control its progression. In the present study, taking advantage of a human superoxide dismutase-1 mutant (hSOD1-G93A) mouse that recapitulates key pathological features of human ALS, we investigated the possible role of voltage-gated potassium channel Kv1.3 in disease progression. We found that chronic administration of the brain-penetrant Kv1.3 inhibitor, PAP-1 (40 mg/Kg), in early symptomatic mice (i) improves motor deficits and prolongs survival of diseased mice (ii) reduces astrocyte reactivity, microglial Kv1.3 expression, and serum pro-inflammatory soluble factors (iii) improves structural mitochondrial deficits in motor neuron mitochondria (iv) restores mitochondrial respiratory dysfunction. Taken together, these findings underscore the potential significance of Kv1.3 activity as a contributing factor to the metabolic disturbances observed in ALS. Consequently, targeting Kv1.3 presents a promising avenue for modulating disease progression, shedding new light on potential therapeutic strategies for ALS.